Climate capitalism and state-owned enterprises (SOES): Case studies of FELDA and FGV palm oil sector / Vignaa Ganesan - Vignaa , Ganesan (2021)
Neoliberalism is often seen as incompatible with sustainability objectives, as profit-seeking firms are expected to overlook climate and environmental concerns in their pursuit to generate revenue. However, the climate capitalism model argues that profit and sustainability goals are not necessarily incompatible. It posits that, under favourable market and governance conditions, private firms can be empowered to shift to more sustainable practises while profiting from this change. Many policymakers have embraced this model as a way to address environmental problems within the context of maintaining existing power structures and for continued economic growth. However, the climate capitalism model has overlooked an important point: a large segment of firms involved in climate-intensive sectors are not private firms. In many natural resource-rich countries, state-owned enterprises (SOEs) control these resources. Hence, this thesis questions the applicability of the climate capitalism model within the context of SOEs. There are many types of SOEs, with different ownership and control structures, which translates to a different emphasis on profit. Therefore, this thesis asks the question: do ownership and control structures of different types of SOEs influence their decision-making processes on the environment? To illustrate this, the thesis uses a case study approach comparing two types of SOEs within the climate intensive palm oil sector: the people-oriented FELDA and the profit-oriented FGV. Despite similar market and governance conditions, the decisions taken by these SOEs resulted in opposite outcomes for the environment. FGV, with an ownership and control structure dominated by state and private investors, tended to take advantage of this structure to overlook environmental objectives in the pursuit of profits. On the other hand, FELDA, which is owned and controlled by the state and settler cooperatives, achieved both capital accumulation and environmental protection through environmentally- and socially_conscious decision making. Hence, even when market and governance conditions are favourable, as in the case of both FELDA and FGV, the ownership and control structures of a firm can influence decision-making to either be positive or negative for the environment. Therefore, this thesis highlights the limitations of the climate capitalism model in predicting the environmental outcomes of neoliberal-type (profit_oriented) SOEs. While its principles may be applicable for most private firms, climate capitalism overlooks the fact that the market is made up of many different types of firms with a variety of ownership and control structures, which can affect firms' decision_making processes. In a world where SOEs control a significant proportion of climate_intensive sectors, there is an urgent need for this influential model to be reconceptualized to accommodate SOEs and other types of firms, to better offer solutions for environmental problems to be addressed within the context of existing institutions, power structures, and continued economic growth.